2018
DOI: 10.5194/soil-4-153-2018
|View full text |Cite
|
Sign up to set email alerts
|

Hot regions of labile and stable soil organic carbon in Germany – Spatial variability and driving factors

Abstract: Abstract. Atmospheric carbon dioxide levels can be mitigated by sequestering carbon in the soil. Sequestration can be facilitated by agricultural management, but its influence is not the same on all soil carbon pools, as labile pools with a high turnover may be accumulated much faster but are also more vulnerable to losses. The aims of this study were to (1) assess how soil organic carbon (SOC) is distributed among SOC fractions on a national scale in Germany, (2) identify factors influencing this distribution… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 55 publications
2
19
1
Order By: Relevance
“…SOC recovery was generally within the range of reports from other studies 53,54 and remarkably constant considering the large variation in initial SOC content ( Table 5). Most samples showed a SOC recovery rate of 80-85%.…”
Section: Representative Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…SOC recovery was generally within the range of reports from other studies 53,54 and remarkably constant considering the large variation in initial SOC content ( Table 5). Most samples showed a SOC recovery rate of 80-85%.…”
Section: Representative Resultssupporting
confidence: 85%
“…There are, however, indications that the organic matter present in macroaggregates may be more similar to the fLF stricto sensu than to the oLF released by high-energy sonication 18 . Some authors have even proposed a low-energy sonication step to isolate the pool of free and weakly mineral-interacting organic matter, termed 'intra-aggregate particulate organic matter', iPOM 54 .…”
Section: Discussionmentioning
confidence: 99%
“…2) and are therefore also referred to as ‘Black Sands' ( Vos et al, 2018). Also in parts of Denmark, Belgium and The Netherlands, these ‘Black Sands' are an acknowledged phenomenon and are mostly linked to a specific pedogenesis (podzolization) or land cover history as heathland or peatland ( Thomsen et al, 2008; Sleutel et al, 2008, 2010; Vos et al, 2018). These two factors are probably interlinked, with land use influencing podzolization and vice versa .…”
Section: Discussionmentioning
confidence: 99%
“…Calluna vulgaris , a major heathland plant species, is acknowledged to form specifically resistant plant litter, with high amounts of polyphenolic substances ( Sleutel et al, 2008). Indeed, Vos et al (2018) found that SOC in those soils consisted of up to 85% particulate organic matter. However, some of the northern German SOC‐rich sands are former peatlands, but not complying with our definition of organic soils anymore, or were formed by plaggen manuring ( Vos et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation